2015
DOI: 10.1149/2.0501602jes
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Copper Birnessite, CuxMnOy·nH2O with Crystallite Size Control: Impact of Crystallite Size on Electrochemistry

Abstract: This report describes the first detailed electrochemical examination of a series of copper birnessite samples under lithium-based battery conditions, allowing a structure/function analysis of the electrochemistry and related material properties. To obtain the series of copper birnessite samples, a novel synthetic approach for the preparation of copper birnessite, CuxMnOy·nH2O is reported. The copper content (x) in CuxMnOy·nH2O, 0.28 ≥ x ≥ 0.20, was inversely proportional to crystallite size, which ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Birnessite-layered structure is of resurgent interest for battery applications as an ionic intercalation material373839 and with what appears to be some characteristics of a conversion electrode1415161727. Bi-δ-MnO 2 in alkaline electrolyte is synthesized either by an in-situ formation step1516264041 by discharging a mix of EMD with Bi 2 O 3 and recharging to its charged state to form Bi-δ-MnO 2 (see Methods section) or by ex situ synthesis methods141517232641424344.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Birnessite-layered structure is of resurgent interest for battery applications as an ionic intercalation material373839 and with what appears to be some characteristics of a conversion electrode1415161727. Bi-δ-MnO 2 in alkaline electrolyte is synthesized either by an in-situ formation step1516264041 by discharging a mix of EMD with Bi 2 O 3 and recharging to its charged state to form Bi-δ-MnO 2 (see Methods section) or by ex situ synthesis methods141517232641424344.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting composite material benefits from enhanced charge transfer and complete regeneration of layered materials on each cycle. The application of this methodology is not only limited to batteries but also applies to areas where layered materials are of interest like oxidation catalysts 36 , intercalation chemistry 37 38 39 and membranes for removal of heavy-metal ions 54 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in d001 spacing of NaB is likely due to the ion exchange of Na + with Cu 2+ from the saline, leading to a transformation of a fraction of Na-birnessite into Cu-birnessite. 57 These observations demonstrate that when NaB/C electrode was cycled in a 100 ppm Cu 2+ saline, Cu 2+ ions were intercalated into the interlayer spacing of the pristine NaB during each ion adsorption operation, whereas a fraction of the intercalated Cu 2+ ions and the original stabilizing Na + ions were deintercalated from the interlayer region simultaneously in each ion desorption operation, leading to a gradual structural evolution of Na-birnessite to a mixture of poorly-crystallized Cu-birnessite, Cu-buserite, and the cycled Na-birnessite. 51,56,57 The phase transformation is also likely to occur in the cases of KB/C and MgB/C electrodes cycled in Cu 2+ saline (Figures S17B, 5A), although the peaks corresponding to the Cu-buserite in the XRD pattern of KB/C after 60 cycles are difficult to be identified (Figure S17B).…”
Section: Mechanisms For Copper Ions Sequestrationmentioning
confidence: 99%
“…69 The last diffractogram of Na-MnO 2 material, as shown in (Figure 1) had well-defined with symmetrical diffraction peaks (001) and (002) (JCPDS card #01-073-9669). 70 They indicated that material was single-phase mineral and well crystallized. This phase corresponds to the family of birnessite type sodium manganese, which has a layered structure with crystal water and Na + between the MnO 6 octahedral sheets.…”
Section: Xrd Of Mno 2 Lamellar and Nanostructuresmentioning
confidence: 99%